Who Becomes a Killer? Explaining Why Most High-Risk Individuals Never Commit Homicide - Zul Khaidir Kadir (Punggawa Global Research: Jurnal Multidisiplin, 2026)
Homicide research is much better at identifying people associated with serious violence than at explaining why only a small minority of high-risk individuals ever kill. The gap is obscured when homicide is treated as the extreme end of a single violence continuum. This article separates violence risk from lethality risk. The first concerns whether serious violence is likely to occur, whereas the second concerns whether a violent episode produces death. An integrative conceptual review of peer-reviewed journal articles published between 2020 and 2026, supplemented by foundational work on situated violence and weapon lethality, is used to develop a Homicidal Threshold Model. The threshold is not a numerical score or a stable property of an offender. It refers to an event condition in which serious violence becomes capable of producing death because the immediate motive and setting make lethal action feasible while effective restraints are absent, weakened, or bypassed. This formulation gives near-lethal incidents a central role. A victim may survive because an attack is interrupted, a weapon fails, an injury is less severe, or trauma care is reached quickly, even when the preceding configuration closely resembles a completed homicide. HTM is therefore limited to lethal differentiation where serious violence is already plausible and death is not predetermined. Its main implication is methodological. Completed homicide should be compared with attempted homicide, near-lethal injury, and closely matched serious non-lethal violence if the field wants to explain the boundary between violence and death rather than repeatedly rediscover broad correlates of dangerousness.